Analisis Faktor yang Berhubungan dengan Rendahnya Pemilihan Alat Kontrasepsi Bawah Kulit (AKBK) di Desa Tirem - Mawadah Mawadah; Nur Anita (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
An introductory survey conducted in Titem Village, Working Area of the Lebak Wangi Health Center in October 2022, out of 940 couples of childbearing age, only 0.3% used contraceptive implants. The results of interviews conducted with 10 acceptors, 70% of people said they did not choose implant contraception because of a lack of knowledge about implant contraception, their husbands were not supportive and the information was not clear about implant contraception. The purpose of this study was to analyze factors related to the low selection of subcutaneous contraceptive devices (AKBK) in Tirem Village, Working Area of the Lebak Wangi Health Center in 2022. This research method used an analytical survey with a cross-sectional design. The sample in this study were 99 respondents of fertile age couples, the sampling technique was purposive sampling. Data analysis using chi square. The results of the study showed that there was a significant relationship between attitude (P-Value = 0.033), husband's support (P-Value = 0.045) and the low selection of Under-the-Skin Contraceptive Devices (AKBK) in Tirem Village, Lebak Wangi Health Center Work Area in 2022. So that research is expected This is able to provide education and information in the selection of subcutaneous protective equipment (AKBK).